2016
DOI: 10.2147/rrn.s95455
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for admission and neonatal outcome in the neonatal care unit of a tertiary care hospital in Addis Ababa: a prospective study

Abstract: Background:The neonatal mortality rate in Ethiopia remains greater than 35 per 1,000 live births. Hence, identifying the reasons for neonatal admission and mortality in a hospital setting is crucial to improve the quality of existing practices in the hospital. The objective of this study was to describe the reasons for admission and the magnitude of neonatal mortality in the neonatal care unit of St Paul's Hospital Millennium Medical College. Methods and subjects: A prospective cohort study was conducted. A to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

24
57
4
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(91 citation statements)
references
References 15 publications
24
57
4
2
Order By: Relevance
“…On the other hand, the magnitude of NMR in the current study is lower as compared to the findings of the studies done at University of Gondar referral hospital-252 [30], Paul's Hospital Millennium Medical College Addis Ababa-232 [31], Pakistan Health Survey of 2014-680 [32] and University of Gondar comprehensive Specialized hospital (UoGCSH)-288 [33]. The variation in the magnitude of NMR could be secondary to the difference in the scope of the study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, the magnitude of NMR in the current study is lower as compared to the findings of the studies done at University of Gondar referral hospital-252 [30], Paul's Hospital Millennium Medical College Addis Ababa-232 [31], Pakistan Health Survey of 2014-680 [32] and University of Gondar comprehensive Specialized hospital (UoGCSH)-288 [33]. The variation in the magnitude of NMR could be secondary to the difference in the scope of the study.…”
Section: Discussioncontrasting
confidence: 81%
“…The variation in the magnitude of NMR could be secondary to the difference in the scope of the study. It is observed that some other previous studies were conducted in a single centered institution which might have lacked representativeness unlike the current one [30,31,33]. The disparity also could be linked to discrepancy in sample size.…”
Section: Discussionmentioning
confidence: 72%
“…In the current study, males were higher in number 1069 (60%) at admission which is in agreement with studies done in Ethiopia, Gonder (58.3%), in St Paul's Hospital Millennium Medical College (61.1%) and other developing countries like South Africa (57.8%) India (63.3%) Pakistan (63%). 15,[19][20][21][22] The reasons could be due to cultural and societal factors in some society's male babies have more attention from caregivers than females. Male neonates also outnumbered females with respect to mortality (62.4%).…”
Section: Discussionmentioning
confidence: 99%
“…The odds of death were increased by nine times for a neonate with the first minute APGAR score < 7 at birth as compared to the counterpart with. The results were obtained from the Iran [24], Nigeria [25], Tikur Anbesa specialized hospital, Ethiopia [26], University of Gondar hospital. Ethiopia [7].…”
Section: Discussionmentioning
confidence: 99%